Implementation of Strategic Management at Ibnussabil Santan Tengah Islamic Boarding School - Muammar Tasbih (Edumaspul: Jurnal Pendidikan, 2023)
The strategic management of the Ibnussabil Islamic boarding school is the primary reference for making programs. For that, continue to grow and develop. So the purpose of this study is to provide an overview of strategic management in this Islamic boarding school, especially its implementation. The research method used is qualitative descriptive with data collection techniques in interviews with specific samples, observations, and documentation studies. From research, it is known that the formulation of strategies is carried out before the Islamic boarding school runs and is carried out by the leaders themselves, without involving other people. The implementation of the system has gone well but still needs to be improved with evaluation because there are still shortcomings. One of the drawbacks is that some programs are not implemented due to funding constraints or unsupportive costs